Optimization of heavy metals removal from aqueous solution using magnesium-aluminium nitrate and intercalated magnesium-aluminium-tartrate layered double hydroxides / Maszlin Mohamad - Mohamad, Maszlin (2015)
Mg-AI-N0₃ and intercalated Mg-Al-tartrate layered double hydroxides were synthesized by co-precipitation method for the removal of lead, cadmium and copper from aqueous solutions. The characterization of Mg-AI-N0₃ by using XRD analysis showed the presence of sharp peaks which signifying high crystallinity. The presence of sharp and intense lines with d-spacing of 7.95 A demonstrated general features of layered double hydroxides. The basal spacing for Mg-Al-tartrate was recorded at 8.14 A which indicates larger d-spacing as compared to the Mg-AI-N0₃. The FTIR analysis showed the strong absorption band was recorded at 1631 cm־¹ for Mg-AI-N0₃ tartrate which attributed to the symmetric and asymmetric vibration of coordinated -COO' group from organic acids. The two stretching vibrations of the alcoholic groups in tartrate are centered at 1111 cm־¹ and 1066 cm־¹ which recorded at 1140 cm־¹and 1082 cm־¹ for the intercalated spectrum. The effects of various experimental parameters on the removal of heavy metals such as contact time, different concentration, pH solution, and adsorbent dosage were investigated by batch method at temperature of 25°C. The percentage removal of heavy metal ions for each of the parameters studied was determined by ICP-OES. The extent of heavy metals ions removal increased with the increased in contact time and the dosage of LDHs used. The higher percentage removal by Mg-Al-tartrate is mainly due to the function of organic anion in the layer which possibly forms complexes with heavy metals. The adsorption experiments of heavy metal solution with high acidity or alkalinity are not desirable in which at high acidity the LDHs will dissolve and at alkaline condition the heavy metals ions are likely to form insoluble precipitates with NaOH. Kinetic study showed that the adsorption of heavy metal ions on LDHs was a gradual process and pseudo second-order rate equation was able to provide realistic description of adsorption kinetics based on equilibrium loading value of experiment (qexp). The shape of the isotherms that obtained from the experimental data was recorded well fitted to the Langmuir isotherm with regression coefficient near to one. The RSM based on a three and four-level CCRD was employed to evaluate the interactive effect of the various optimization parameters. The experimental percentage recorded under optimum conditions was compared well with the maximum predicted value from the RSM with not more than 1%of differences, which suggest that CCRD of RSM can be used to study the removal of heavy metal ions from aqueous solution.